دور الموازنة بين العائد و المخاطرة في تصويب الاعتبارات الشخصية للمستثمرين عند إختيار السلوك المالي - بن نوار, عمار; كاف, محمد رياض (Université de M'sila, 2016)
The study aims to select a right financial behavior according to scientific bases and at the same time does not eliminate the psychological and behavior of the investor, Meaning the selection of financial decisions that have certain degree of the risks which are acceptable to the investor, Provided that the expected benefits of them would be suitable for the degree of risk that accept endure. Considering that making financial decision process is closely related to the psychological characteristics of the financial manager and nature of the investor, and the degree of satisfaction who wishes to achieve, whereas likely that the manager is characterized by one of the following attributes (Adventurous, Conservative, Optimization) ,It located under this influence that leading to especial opinions and perceptions towards certain behavioral financial phenomena . Study concluded that the relationship between return and risk is proportional, And the compensatory relationship between return and risk that obliges the financial decision maker determines the balanced combination between return and risk ,Through their appreciation of return is expected to get it and that creates has a satisfaction according to the degree of risk accepted by him, By Measurement Quantitative of these decisions using mathematical models that provided good explanations for the relationship between return and risk. Keywords:return, risk, financial behavior, the balance between return and risk, the behavioral aspects of financial decisions, choosing financing decision.